Hydrogeology and hydrogeochemistry of the Zaeltsovsko-Mochishchensky zone of radon waters in the southern West Siberia - D. A. Novikov; A. F. Sukhorukova; T. V. Korneeva (Геодинамика и тектонофизика)
The study aims at solving the fundamental and applied problems of hydrogeology and hydrogeochemistry of the Zaeltsovsko-Mochishchensky zone of radon waters in the northwestern district of the city of Novosibirsk. Novosibirsk is one of the few Russian cities built on granites that emit radon (222Rn). In geological terms, the study area is confined to the NW near-contact zone of the large Novosibirsk granitoid massif. The available data on radon in this area has not been scientifically consolidated yet. We used the methods of S.L. Shvartsev, N.M. Kruglikov, V.V. Nelyubin, O.N. Yakovlev, and V.M. Matusevich and software packages Visual Minteq, PhreeqC, WATEQ4f and HG-32 and obtained physical and chemical calculations for the forms of migration of trace elements in radon waters and estimated the degrees of radon water saturation with rock-forming minerals. The data from hydrogeological profiles and hydrogeochemical sampling (118 samples from 57 water wells and sources) were analyzed. Radon waters are fissure-type, cold (6–10 °С) and occur at a depth of 50–200 m. By their chemical composition (according to the classification proposed by S.А. Shchukarev), the waters are mainly hydro-carbonate calcium and hydro-carbonate calcium-sodium; the total mineralization amounts to 322–895 mg/dm3. All the water wells drilled in granites and near-contact hornfels were tested for radon. It is revealed that the 222Rn concentration in water varies widely, from 11 to 801 Bq/dm3. Therefore, such waters are classified as low-radon and moderate-radon mineral waters (according to the classification proposed by N.I. Tolstikhin). In the wells drilled in hornfels, the 222Rn concentration in water is 37–241 Bq/dm3. The concentrations of 238U and 226Ra do not exceed 0.098 and 1.9∙10–9 mg/dm3, respectively. Physicochemical simulation shows that Ag+, Ba2+, Zn2+, Ni2+, Mn2+, Sr2+, Fe2+ migrate mainly as free ions, while Be2+, Fe3+, Zr4+, Ti4+ migrate as hydroxide complexes. Uranium is mainly present in uranyl-carbonate complexes of calcium: Ca2UO2(CO3)3(aq) (61–75 %) and CaUO2(CO3)32– (25–36 %). Calculations show abundant saturation of the waters with calcite, dolomite, ferrihydrite, greenalite, hausmannite, manganite, quartz, rutile, siderite, lepidocrocite, goethite, and pyrolusite. The mineral phases, such as aragonite, barite, chalcedony, cristobalite, vaterite, and amorphous silicon dioxide are in equilibrium. Several samples show saturation of the waters with relatively rare phosphorus-containing minerals: hydroxyapatite, manganese hydrogen phosphate, cerargyrite, and lead molybdate. The radon waters are not saturated with monohydrocalcite, calcium molybdate, celestite, chrysotile, copper hydroxide, copper molybdate, epsomite, huntite, amorphous and crystalline iron hydroxide (II), gypsum, iron molybdate (II), magnesite, lansfordite, Na-jarosite, nesquehonite, powellite, strontianite, tenorite, witherite, and zirconium dioxide.